Local and Extended-Order Evolution of Synthetic Talc during Hydrothermal Synthesis: Extended X-ray Absorption Fine Structure, X-ray Diffraction, and Fourier Transform Infrared Spectroscopy Studies - Dumas, Angela (2015)
Synthetic talc is a newfiller of industrial interest due to its submicronsize, its chemical and mineral purity, and its hydrophilic character. To develop this filler on a preindustrial scale, this work aimed to understand the mechanisms of transformation from the amorphous talc precursor to crystalline synthetic talc. X-ray diffraction, Fourier transform infrared spectroscopy, and extended X-ray absorption fine structure at Ni−K edge techniques were used to study a Ni-talc series composed of a talc precursor sample and talc samples synthesized at 100, 200, and 300°C for 1 or 6 h. As soon as the Ni-talc precursor precipitated, a tetrahedral−octahedral−tetrahedral-type structure appeared that was characterized by 2−3 Ni-octahedra distanced 3.07 Å from each other and by 3−4 Si tetrahedra distributed on the top and bottom of the octahedral"sheet" and distanced 3.29 Å from Ni. Simultaneously following the synthesis temperature, the octahedral sheet grew, and the tetrahedral sheet expanded; the distances Ni−Ni and Ni−Si also gradually shortened. The intracrystalline distribution of the octahedral sheet was also studied. At 300 °C, a random distribution was obtained. Cluster distribution was not observed at low temperature, which we hypothesize is a function of crystallite size.